Editorial Vol7 no1 - Irene Stevens (Scottish Journal of Residential Child Care)
It is hard to believe that the Scottish Journal of Residential Child Care has entered its sixth year of publication. In the first issue of the journal, we expressed our hopes that the journal would help us to look at developments in practice, policy, research and training at every level of residential child care. It was also one of our greatest hopes that the journal would help in 'breaking down some of the barriers between practice and research' (Kendrick, 2002, p. 5). This prompted some reflection on the types of articles we have received and published over the years. Has the journal lived up to its promise?